"Fight or flight": coping responses to brand hate. Issue 3 (22nd December 2020) - Bayarassou, Oula; Becheur, Imene; Valette-Florence, Pierre
Abstract : Purpose: This study aims to investigate the interplay between brand and consumer personalities in shaping brand hate and its consequences. More specifically, it investigates the relationship between fallacious character of the brand, brand betrayal feelings and brand hate, and identifies two response routes leading to consumer avoidance and revenge. Furthermore, the study explores the moderating impact of narcissism on the relationships between brand hate and its outcomes. Design/methodology/approach: Data are collected from an online survey of a French representative consumer panel where participants were asked to cite a particular brand they hate, and then assess the different constructs tested in the model. Partial least squares structural equation modeling was used for data analysis. Findings: The study sheds light on the possible mediators and moderators of brand hate. Particularly, brand betrayal is hypothesized as a mediator between fallacious character of the brand and brand hate. Moreover, the study assesses the impact of narcissism on the relationship between brand hate and desire for avoidance and revenge. Findings show that active brand hate leads to a desire for revenge, whereas passive brand hate positively influences desire for avoidance. Finally, the current research suggests that consumer narcissism fuels desire for revenge on the brand. Originality/value: To the authors' knowledge, this study is the first to integrate brand personality (the fallacious character of the brand) and consumer personality (narcissism). The study describes the mechanism through which brand transgressions activate two response routes to brand hate associated with the desires for revenge and avoidance.